Investigação molecular de alphavirus em pacientes febris durante epidemia de dengue em Mato Grosso, Brasil - Zuchi, Nayara (2014)
Introduction: The Alphavirus genus, Togaviridae family, comprises arboviruses of medical importance reported in tropical areas worldwide. In the Americas, the most important alfaviruses are the equine encephalitis group and Mayaro virus (MAYV). In Brazil, MAYV has been reported in outbreaks of febrile illness mainly in the North region of the country. The aim of this study was to investigate the epidemiological situation of alfaviruses in febrile patients during a dengue outbreak in Mato Grosso (MT). Material and methods: Between 2011 and 2012 in MT, 604 serum samples collected from patients suspected of acute febrile illness were submitted to Duplex-RT-PCR followed by Multiplex-semi-nested-PCR for MAYV, Aura virus and East, West and Venezuelan equine encephalitis viruses. Positive samples were confirmed twice in independent tests and, PCR products were submitted to nucleotide sequencing. Positive samples were also submitted to Real time RT-PCR (RT-qPCR) and inoculation in cell culture. The samples were also investigated for flaviviruses in a parallel study. Amostras positivas foram submetidas a RT-PCR em tempo real (RT-qPCR) e isolamento viral em cultura de células. Todas as amostras foram também investigadas para flavivirus em um estudo paralelo. Results: 15/604 (2.5 %) patients from Cuiabá (9), Várzea Grande (3), Nossa Senhora do Livramento (1) and Sorriso (2) were positive for MAYV; 12 (80 %) are co-infected with DENV-4 and 3 (20 %) are single infections with MAYV. Co-infected patients presented a wider variety of clinical manifestations. Among 13 samples tested by RT-qPCR, 10 (76.9 %) presented viral load ranging from log 0,965-3,321 copies/μL. Discussion: Sporadic infections with MAYV were identified during a massive Dengue outbreak in MT in residents of urban areas without recent history of travel or visit to rural or sylvatic areas. The occurrence of MAYV infections in neighboring states, including cities affected by the Cuiabá-Santarém highway and seroprevalence in Xavante Indians from MT, corroborate the evidence of MAYV circulation in MT. Despite MAYV is transmitted mainly by Haemagogus janthinomys in sylvatic areas, the evidence found in this study suggests the circulation of MAYV in urban areas of MT. However, the transmission cycle of MAYV in MT remains to be determined. The evidence of MAYV circulation in febrile individuals during a dengue outbreak in urban areas should cause concerns in the local public health authorities about the eventual silent circulation of arboviruses in the state.